Prenatal exposure to persistent organic pollutants modulates the metabolism and gut microbiota of the offspring - Lamichhane, Santosh; Salihovic, Samira; Sinioja, Tim; Virtanen, Suvi M.; Vatanen, Tommi; Orešič, Matej; Knip, Mikael; Hyötyläinen, Tuulia (Elsevier, 2026)
Emerging evidence suggests that environmental contaminants can influence both human metabolism and gut microbiota composition. However, the specific effects of prenatal exposure to persistent organic pollutants (POPs) on host–microbiome metabolic interactions remain incompletely understood. In this study, we investigated associations between prenatal exposure to POPs, including organochlorine pesticides, polychlorinated biphenyls (PCBs), and per- and polyfluoroalkyl substances (PFAS), and growth, metabolic profiles, and gut microbiota composition in infants at three months of age. Prenatal POP exposure was strongly associated with alterations in the infant metabolome, particularly affecting lipid metabolism and microbiota-derived metabolites. Among the POPs examined, PCBs showed the most pronounced influence on both metabolic profiles and gut microbial composition. The most affected metabolic pathways included fatty acid metabolism, bile acid transformation, and steroid hormone biosynthesis. Furthermore, prenatal POP exposure significantly altered the composition of the gut microbiome. PCB exposure was linked to reduced Bifidobacterium bifidum and Lactobacillus paragasseri, and increased Erysipelatoclostridium ramosum, along with disruptions in bile acid and amino acid metabolism. These findings suggest that early-life exposure to POPs can disrupt host–microbiome metabolic interactions, potentially through perturbation of lipid- and amino acid–related pathways.